PENGARUH KUALITAS PELAYANAN DAN KEPUASAN PASIEN TERHADAP LOYALITAS PASIEN MELALUI CITRA MEREK PADA RUMAH SAKIT SWASTA DI JAKARTA - Mochamad Ichsan, .. (2017)
This study was conducted to examine the contribution (contribution) filed by path analysis on any causal relationship between the variables of service quality and patient satisfaction with loalitas patient through brand image.The population in this study were residents around the Village West Pejaten Pasar Minggu ever used the services of outpatient at Castle Hospital Cinere. In this study used a sample of 100 respondents. Sampling technique using a non-probability sampling with purposive sampling technique.The analysis technique used in this study using Path Analysis (Path Analysis). The results showed that the direct effect of service quality on a significant and positive brand image by 0.330. The direct effect of patient satisfaction with the positive brand image and not significant at 0.110.The direct effect of service quality to a significant and positive patient loyalty by 0.605 if through a brand image for -0.027. Direct influence patient satisfaction with patient loyalty negative and not significant at -0.479 if through a brand image by -0,009. The direct effect of brand image to negative patient loyalty and not significant at -0.083. Therefore, the direct effect had a greater influence than pengaeuh indirectly so as not effective for increasing loyalty, it can be concluded that the patient will not be loyal to the hospital, although they felt satisfied with the quality of services provided hospital.